Diseño y simulación de un medidor volumétrico patrón (MVP) con capacidad de 100 galones para la determinación estática de hidrocarburos en los procesos intervenidos por la empresa SERVITEINS J&I SAS (2021)
One of the main economic activities in the department of Huila is the exploitation of hydrocarbons. However, it lacks an adequate metrological infrastructure for the calibration of instruments for measuring volume. The inconveniences generated can be varied, from the increase in operating costs to the non-assurance of industrial processes. Therefore, in this work we design and simulate a standard volumetric meter (MVP) appropriate to the technical requirements of the company SERVITEINS J&I S.A.S. and local industry demands. For this purpose, bibliographic and documentary research was carried out on the central issues, detailed analysis of volume measurement in hydrocarbon processes, and the design of a device according to parameters identified in periodic visits to the company, procedures identified in the specialized bibliography and recommendations of MANUAL NBS 105-3, ISO 17050, ISO 17025, ISO 10012, OIML R 120: 2010. The main components are; (i) flow straightener, to reduce fluid turbulence; (ii) A control valve, for safety in the measurement process; (iii) A programmable logic controller (PLC), to control the process. The entire design was validated via simulation in SolidWorks and Factory talk view. As a result, the design and simulation of a 100-gallon standard volumetric meter with non-turbulent fluid was obtained.